(untitled) (EAAE Annual Conference Proceedings, 2024)
Embark on the journey towards a more graceful future today! Our dynamic ecosystem is in perpetual evolution. As architects and planners, we play a pivotal role in shaping it. In educating aspiring architects, planners and de- signers, as well as in conducting research on all facets of the built environ- ment, there is a pressing need to prioritize sufficiency and embrace interdis- ciplinary approaches as never before. We eagerly anticipate a multitude of perspectives, bold collaborations and profound revelations as we convene for our annual gathering in Münster: Let us engage in open dialogue, spark- ing inspiration and mutual enrichment.